Anesthetic management of parturient with thoracic kyphoscoliosis, malaria and acute respiratory distress syndrome for urgent cesarean section - Ravindra Kr Pandey; Meenu M Batra; Vanlal Darlong; Rakesh Garg; Jyotsna Punj; Sri Kumar (Wolters Kluwer Medknow Publications, 2015)
The management of cesarean section in kyphoscoliotic patient is challenging. The respiratory changes and increased metabolic demands due to pregnancy may compromise the limited respiratory reserves in such patients. Presence of other comorbidities like malaria and respiratory tract infection will further compromise the effective oxygenation. We report a case of kyphoscoliosis along with malaria and acute respiratory distress syndrome for urgent cesarean section.